Prevalence and incidence of patients with generalized pustular psoriasis in Denmark-A nationwide registry‐based study - Jeanette Halskou Haugaard; David Thein; Alexander Egeberg (Wiley, 2023)
Abstract Background Generalized pustular psoriasis (GPP) is an inflammatory skin disease characterized by episodic flares of erythematous painful skin with widespread sterile pustules. The disease is a rare and potentially life‐threatening variant of psoriasis. To date, little is known about the incidence and prevalence of GPP; possibly due to the rarity of the disease. Objectives The objective of this study was to examine the incidence and prevalence of patients with GPP in Denmark. Methods The incidence and prevalence of GPP were calculated based on data from the Danish nationwide administrative registries. We identified patients with incident GPP as those recorded with a first‐ever diagnostic code for GPP between 1 January 1997 and 31 December 2018. The prevalence of GPP was estimated based on all Danes alive and resident in the source population on 31 December 2018. Results The incidence rates of GPP varied from 0.14 to 0.43 per 100,000 person‐years in a period spanning 22 years (1997-2018). There was generally a strong female predominance among patients diagnosed with GPP, and mean age at the time of diagnosis varied from 47 to 64 years in the study period. We estimated the lifetime prevalence of GPP to be 0.0111%, or 11.1 per 100,000 Danish residents. Conclusions Our findings indicate that the incidence rates of GPP have remained stable in a time‐period spanning 22 years from 1997 to 2018, however, the rate of inpatient hospitalizations did appear to be somewhat decreasing in more recent years.